2021
DOI: 10.1021/acs.jpcc.0c09554
|View full text |Cite
|
Sign up to set email alerts
|

Lead-Free Alloyed Double-Perovskite Nanocrystals of Cs2(NaxAg1–x)BiBr6 with Tunable Band Gap

Abstract: Lead-free halide double perovskites (DPs) have emerged as a stable and greener alternative to very toxic lead-based perovskites owing to their outstanding photophysical properties. Here, a series of Cs 2 (Na x Ag 1−x )BiBr 6 (x = 0, 0.25, 0.5, 0.75, and 1) double-perovskite nanocrystals (NCs) are synthesized, which have not been much explored yet. The formation of highly miscible Cs 2 (Na x Ag 1−x )BiBr 6 solid solutions is favored because of very low lattice mismatch between Cs 2 NaBiBr 6 and Cs 2 AgBiBr 6 . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 66 publications
0
34
0
Order By: Relevance
“…Over the past few years, lead-free all-inorganic double perovskites with formula A 2 B′B″X 6 have emerged as possible contenders due to low toxicity, intrinsic thermodynamic stability, and small carrier effective mass. In particular, the double perovskite Cs 2 AgInCl 6 has been the subject of several studies, revealing excellent environmental stability and promising optoelectronic properties. For example, Cs 2 AgInCl 6 double perovskite exhibits a direct band gap as well as an ultralong carrier lifetime (6 μs), which are suitable for photovoltaic applications. Note that Cs 2 AgInCl 6 has been successfully synthesized experimentally with the direct band gap of 3.3 eV, 3.5 eV, and good thermodynamic stability .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, lead-free all-inorganic double perovskites with formula A 2 B′B″X 6 have emerged as possible contenders due to low toxicity, intrinsic thermodynamic stability, and small carrier effective mass. In particular, the double perovskite Cs 2 AgInCl 6 has been the subject of several studies, revealing excellent environmental stability and promising optoelectronic properties. For example, Cs 2 AgInCl 6 double perovskite exhibits a direct band gap as well as an ultralong carrier lifetime (6 μs), which are suitable for photovoltaic applications. Note that Cs 2 AgInCl 6 has been successfully synthesized experimentally with the direct band gap of 3.3 eV, 3.5 eV, and good thermodynamic stability .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to reduce its band gap and expand the spectral response in the visible light region, alloying with suitable elements could be the best solution. Incidentally, it has been already reported that the alloying of a metal cation (viz., Na) in these types of halide double perovskites helps in modulating the band gap alongside enhancement of the photoluminescence efficiency. ,,, Also, the exciton binding energy of Cs 2 AgInCl 6 has been calculated to be 0.25 eV using GW-BSE calculations (G indicates the single-particle Green’s function; W indicates the screened Coulomb interaction; BSE indicates the Bethe-Salpeter equation) . Now, to enhance the optical properties, sublattice mixing by partial substitution of several metals M­(I), M­(II), M­(III), and halogen X at Ag/In and Cl sites, respectively, is reported to reduce the band gap of Cs 2 AgInCl 6 .…”
Section: Introductionmentioning
confidence: 99%
“…S2, ESI †). 17 Instead, structural defects such as interstitial doping are likely generated as the amount of dopant increases. The actual Mn content in the lattice was only 2% (Table S1, ESI †), which was much lower than the nominal concentration (20%).…”
mentioning
confidence: 99%
“…47 Apart from the role as dopants, Bi 3+ , Sb 3+ and Te 4+ have also been successfully used as ideal B-site cations in order to provide alternative lead-free perovskite semiconductors for optoelectronic applications. 30,48,49 So far, 0D perovskites possessing STE emission characteristics based on their transient lattice deformation upon photoexcitation have been reported. 50,51 While undoped Cs 2 SnCl 6 does not possess any PL, an incorporation of a small percentage of one of the aforementioned dopants results in visible PL with high PLQY.…”
Section: Introductionmentioning
confidence: 99%